Patrimônio geológico no Parque Estadual Turístico do Alto Ribeira - SP: inventariação e quantificação de geossítios - Ferreira, Ana Rita Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Due to its natural and cultural diversity, Brazil has a high potential for both to the development of geotourism as for the creation of Geoparks. Since geoconservation is a very recent branch of geosciences in Brazil, there is still a long way towards the systematization of knowledge about the national geological heritage. The geoconservation assumes not only of strategic importance to the growth of tourism in Brazil, but also can be a tool for socioeconomic and educational development. The Alto Ribeira State and Tourist Park (PETAR) is one of the oldest protected areas in the state of São Paulo, created in 1958. It has an area of 35.102.8 hectares and is located in the Ribeira Valley, in the southwest of São Paulo state. The importance of the area is the result of the association between the Atlantic Forest reserve with an exceptional biodiversity and karst systems whose unique underground scenario combines a variety of forms of speleothems. The area presents distinct tectonic environments that represent the Precambrian geological evolution of the south-southeastern Brazil, therefore the geological heritage in PETAR acquires a great value. PETAR represents one of the most important speleological regions of Brazil with more than 400 registered caves, a variety of waterfalls, viewing points, trails and traditional communities. The Karst and Caves of the Alto Ribeira State and Tourist Park were already recorded and described by SIGEP and, according to CPRM (2002), the Alto da Ribeira is in the list of potential areas to develop the Geopark concept in the Brazilian territory. In the present work, developed in PETAR area, there were inventoried, characterized and quantified 19 geosites, most of them with speleological interest, in which a methodology to quantify their relevance was applied. That allowed ranking the geosites. The inventory was conducted using the following criteria: representativeness, integrity, accessibility, scientific and...

Devido à sua diversidade natural e cultural, o Brasil tem um elevado potencial tanto para o desenvolvimento do geoturismo, como para a criação de geoparques. Visto que a geoconservação é um ramo das geociências muito recente no Brasil, ainda existe um longo caminho em direção à sistematização do conhecimento sobre o patrimônio geológico nacional. A geoconservação assume não só uma importância estratégica para o crescimento do turismo no Brasil, mas também pode ser uma ferramenta para o desenvolvimento socioeconômico e educacional. O Parque Estadual Turístico do Alto Ribeira (PETAR) é uma das mais antigas unidades de conservação no Estado de São Paulo, criada em 1958. Tem uma área de 35.102.8 hectares e localiza-se no Vale do Ribeira, no sudoeste do estado de São Paulo. A importância da área é o resultado da associação entre a reserva de Mata Atlântica com uma excepcional biodiversidade e os sistemas cársticos cujo cenário subterrâneo único combina uma grande variedade de formas de espeleotemas. Na área do PETAR estão presentes distintos ambientes geotectônicos que representam a evolução geológica precambriana da região sul-sudeste do Brasil, conferindo assim uma grande importância ao seu patrimônio geológico. O PETAR representa uma das regiões espeleológicas mais importantes do Brasil com mais de 400 cavernas registradas, uma variedade de cachoeiras, mirantes, trilhas e comunidades tradicionais. O Carste e Cavernas do Parque Estadual Turístico do Alto Ribeira já se encontram registrados e descritos pela Comissão Brasileira dos Sítios Geológicos e Paleobiológicos (SIGEP) e, segundo o Serviço Geológico do Brasil (2002), o Alto da Ribeira está na lista de potenciais áreas para desenvolver geoparques em território brasileiro. No presente trabalho, desenvolvido na área do PETAR, foram inventariados, caracterizados e quantificados 19 geossítios, na sua maioria de interesse espeleológico...
Keywords: Tourism; Turismo; Geodiversidade; Geoturismo; Unidades de conservação; Patrimonio; Geologia - Inventários; Parque Estadual Turístico do Alto Ribeira (SP)